Activity of alemtuzumab monotherapy in treatment-naive, relapsed, and refractory severe acquired aplastic anemia - Hrodek, Otto (Transfuze a hematologie dnes, 2012)
Antithymocyte globulin (ATG) + cyclosporine is effective in restoring hematopoiesis in severe aplastic anemia (SAA). We hypothesized that the humanized anti-CD52 mAb alemtuzumab might be active in SAA because of its lymphocytotoxic properties. We investigated alemtuzumab monotherapy from 2003-2010 in treatment-naive, relapsed, and refractory SAA in 3 separate research protocols at the National Institutes of Health. Primary outcome was hematologic response at 6 months. For refractory disease, patients were randomized between rabbit ATG + cyclosporine (n = 27) and alemtuzumab (n = 27); the response rate for alemtuzumab was 37% (95% confidence interval [CI], 18%-57%) and for rabbit ATG 33% (95% CI, 14%-52%; P = .78). The 3-year survival was 83% (95% CI, 68%-99%) for alemtuzumab and 60% (95% CI, 43%-85%) for rabbit ATG (P = .16). For relapsed disease (n = 25), alemtuzumab was administered in a single-arm study; the response rate was 56% (95% CI, 35%-77%) and the 3-year survival was 86% (95% CI, 72%-100%). In treatment-naive patients (n = 16), alemtuzumab was compared with horse and rabbit ATG in a 3-arm randomized study; the response rate was 19% (95% CI 0%-40%), and the alemtuzumab arm was discontinued early. We conclude that alemtuzumab is effective in SAA, but best results are obtained in the relapsed and refractory settings. The present trials were registered at www.clinicaltrials.gov as NCT00195624, NCT00260689, and NCT00065260.
Keywords: výsledek terapie; Young Adult; Salvage Therapy; Male; Child, Preschool; Immunosuppressive Agents; protinádorové látky; Survival Rate; lokální recidiva nádoru; mladý dospělý; následné studie; Adolescent; Neoplasm Staging; Child; aplastická anemie; dítě; chemorezistence; Adult; protilátky nádorové; dospělí; Aged; mužské pohlaví; senioři; Antibodies, Neoplasm; Prospective Studies; Antineoplastic Agents; králíci; mladiství; Follow-Up Studies; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; Treatment Outcome; předškolní dítě; antilymfocytární sérum; Neoplasm Recurrence, Local; záchranná terapie; Animals; lidé; ženské pohlaví; Humans; zvířata; Cyclosporine; Rabbits; Anemia, Aplastic; cyklosporin; Antilymphocyte Serum; Drug Resistance, Neoplasm; Female; lidé středního věku; staging nádorů; míra přežití; imunosupresiva; Middle Aged; prospektivní studie